EFL Teacher’s Problems and Solutions In Teaching English At A Rural Junior High School - Yensi Kurnia Sari; Mukminatus Zuhriyah (ETERNAL (English Teaching Journal), 2023)
English is considered a foreign language in Indonesia and must be learned by everyone, especially students. The purpose of teaching English in schools is to improve students' communication skills and prepare them for the current era of globalization. However, at SMPN 3 Satap Ngoro, which is a remote school, English teacher face problems in teaching that affect students, the teacher and the environment. In addition, the lack of teacher training results in the quality of teachers at SMPN 3 Satap Ngoro school becoming a problem that greatly affects students' English learning. The purpose of this study is to clarify the problems faced by teacher especially English teacher and to find solutions to the problems faced by teacher in English learning. This case study consists of interviews and observations and is supported by documentation. The researchers found that English teacher at SMPN 3 Satap Ngoro face problems in teaching English because the students are still very dependent on their environment using their local language, namely Madura so that English teacher must understand and understand Madura. The low interest of students in learning English can be overcome by using games or learning outside the classroom that makes them comfortable and happy. In addition, the lack of English learning facilities can be overcome by using the reference handbook that teacher have. Then, the lack of teacher training can also be overcome by substituting for teacher who do not have teaching hours. This researchers will help English teacher improve their English teaching skills especially at SMPN 3 Satap Ngoro as a rural school.